Prevalence of Pulmonary Embolism in COVID-19 Positive Critically Ill Children - Yudy Fonseca, MD; Alise Davies, PA; Stephanie Jarrin, MD; Liliana Simon, MD; Cortney Foster, DO; Sun Kai; Adnan Bhutta, MD (Critical Care Explorations)
OBJECTIVES:. To investigate the prevalence of pulmonary embolism (PE) in children admitted to critical care diagnosed with COVID-19 infection. DESIGN:. Retrospective database study. SETTING:. Data reported to the Virtual Pediatric Systems, 2018–2021. PATIENTS:. Patients 28 days to younger than 18 years old, admitted to a PICU with either PE or COVID-19 diagnoses. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. Among the PE-positive subgroups, from January 2020 to December 2021, 78 patients (14%) had an acute COVID-19 infection. The prevalence of PE pre-pandemic period (2018–2019) was 0.19% and for pandemic period (2020–2021) was 0.26% (p < 0.001). During the pandemic period, the prevalence of PE for COVID-negative patients was 0.21% and for COVID-positive patients was 1.01% (p < 0.001). The result shows that the chance to develop PE for COVID-positive patients is 4.8 times that for COVID-negative patients during the pandemic. In the subgroup of the PE-positive patients, 55.1% were Black or African American in the COVID-positive group and 19% in the COVID-negative group (p < 0.001). A multivariable logistic regression showed that race was an independent risk factor for COVID in PE-positive patients. CONCLUSIONS:. Our study demonstrates a significant increase in the prevalence of PE among pediatric patients admitted to PICUs during the COVID-19 pandemic compared with pre-pandemic. Our study indicates that COVID-positive patients are 4.8 times more likely to develop PE than COVID-negative patients. Additionally, the study highlights substantial racial disparities in the prevalence of PE, with Black or African American patients being disproportionately affected.